2017
DOI: 10.1371/journal.pone.0177960
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of mudskipper (Boleophthalmus pectinirostris) hypoxia-inducible factor-1α (HIF-1α) and analysis of its function in monocytes/macrophages

Abstract: Hypoxia-inducible factor-1α (HIF-1α) plays a critical role in immune and inflammatory responses and is important in controlling a variety of processes in monocytes and macrophages. However, very little information is available about the functions of HIF-1α in fish monocytes/macrophages (MO/MФ). In this study, the cDNA sequence of the mudskipper (Boleophthalmus pectinirostris) HIF-1α gene (BpHIF-1α) was determined. Sequence comparison and phylogenetic tree analysis showed that BpHIF-1α is clustered in the fish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…In this study, most hif genes were down-regulated after A. hydrophila infection in a common carp population. Although the down-regulation of hif1 is rarely observed after bacterial infection, we have found similar phenomena in other studies, such as when Boleophthalmus pectinirostris were infected with Edwardsiella tarda, the expression of hif-1a gene in intestine decreased (Guan et al, 2017). This phenomenon is also found in other genes.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, most hif genes were down-regulated after A. hydrophila infection in a common carp population. Although the down-regulation of hif1 is rarely observed after bacterial infection, we have found similar phenomena in other studies, such as when Boleophthalmus pectinirostris were infected with Edwardsiella tarda, the expression of hif-1a gene in intestine decreased (Guan et al, 2017). This phenomenon is also found in other genes.…”
Section: Discussionsupporting
confidence: 88%
“…The isolation of leukocytes from the AK has been widely explored by centrifugation in density gradients for a long time. Various mononuclear cell separation medium, mainly including Sepracell-MN (no longer manufactured), Percoll (GE Healthcare, Chicago, IL, USA), Histopaque ® -1077 (Sigma, St. Louis, MO, USA), and Ficoll-Paque ® PREMIUM (GE Healthcare, Chicago, IL, USA), have been used to isolate the different cell types in teleost fish (26,55,56). Among these, continuous Percoll density gradients are used to isolate different types of immune cells (monocytes/macrophages, NCCs, and DCs) roughly (44,(57)(58)(59), but Histopaque ® -1077 and Ficoll-Paque ® PREMIUM are used to obtain the leukocytes (a mixture of various immune cells, but not referring to certain cells) (26,60).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the few studies that have measured both hif-1α mRNA and Hif-1α protein levels using homologous antibodies (e.g. Law et al, 2006;Kopp et al, 2011;Guan et al, 2017) demonstrated discrepancies between mRNA and protein levels that may vary with the duration and severity of hypoxia as well as the specific tissues being examined. A second important finding of the Soitamo et al (2001) study was the observation that although Hif-1α protein increases in cultured trout cells exposed to hypoxia, peak levels are achieved with relatively mild exposure (38 mmHg) and actually decrease at the most severe levels of hypoxia employed.…”
Section: Contribution Of the Hif Pathway To Hypoxia Tolerance And Sur...mentioning
confidence: 99%